2004
DOI: 10.1016/j.ymthe.2003.10.012
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Gene-Modified Mesenchymal Stem Cells Promote Functional Recovery and Reduce Infarct Size in the Rat Middle Cerebral Artery Occlusion Model

Abstract: Examination of the clinical therapeutic efficacy of using bone marrow stromal cells, including mesenchymal stem cells (MSC), has recently been the focus of much investigation. MSC were reported to ameliorate functional deficits after stroke in rats, with some of this improvement possibly resulting from the action of cytokines secreted by these cells. To enhance such cytokine effects, we transfected telomerized human MSC with the BDNF gene using a fiber-mutant F/RGD adenovirus vector and investigated whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
225
2
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(241 citation statements)
references
References 47 publications
10
225
2
4
Order By: Relevance
“…In our previous study, we demonstrated that EGFP-BMSCs migrate to hippocampus and cortex regions under ischemia condition after intravenous injection [36], indicating that BMSCs could pass blood-brain barrier and go to hippocampus and cortex. After transplantation into the body, MSCs have shown the ability to differentiate into neuron-like cells that secrete trophic factors such as VEGF [32], BDNF [8], and NGF [37], which play important roles in protecting the injured neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we demonstrated that EGFP-BMSCs migrate to hippocampus and cortex regions under ischemia condition after intravenous injection [36], indicating that BMSCs could pass blood-brain barrier and go to hippocampus and cortex. After transplantation into the body, MSCs have shown the ability to differentiate into neuron-like cells that secrete trophic factors such as VEGF [32], BDNF [8], and NGF [37], which play important roles in protecting the injured neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on stroke using BMSCs as treatment suggest genetic modification of BMSCs to improve therapeutic potential. Indeed, overexpression of trophic factors such as brain-derived neurotrophic factor (BDNF), fibroblast growth factor-2, and hematopoietic growth factor in gene-modified BMSCs has been demonstrated to improve neurologic outcome in animal models of ischemic stroke [7][8][9] Hypoxia-inducible factor-1 (HIF-1) is an oxygen-sensitive transcription factor [10]. HIF-1 is a heterodimeric protein that consists of a functional HIF-1a subunit and a constitutively expressed HIF-1b subunit.…”
Section: Introductionmentioning
confidence: 99%
“…It may indicate that gene transfer with HSV-1 vector ex vivo would not influence the survival and dividing abilities and the therapeutic efficiency of MSCs after transplantation. So far, to reduce the disability resulting from stroke, some studies have focused on the development of neuroprotective agents such as brainderived neurotrophic factor, the fibroblast growth factor that effectively prevents delayed neuronal death after transient brain ischemia (Kurozumi et al, 2004;Watanabe et al, 2004). Recently, overexpression of HGF that can improve the neurological sequalae by neuroprotection, reduce the infarct volume, and the likelihood of brain edema after stroke was reported (Miyazawa et al, 1998;Tsuzuki et al, 2000;Hayashi et al, 2001;Shimamura et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Independent of the cell fusion vs transdifferentiation issue, isolated cultured bone marrowderived MSCs have been shown to secrete trophic factors such as brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), vascular endothelial growth factors (VEGF), and hepatocyte growth factor (HGF) (Hamano et al, 2000;Chen et al, 2002;Iihoshi et al, 2004;Kurozumi et al, 2004). Indeed, BDNF administration has neuroprotective effects in a rat ischemia model (Schabitz et al, 1997(Schabitz et al, , 2000Yamashita et al, 1997).…”
mentioning
confidence: 99%